Do cross listed securities in the face of extreme events present any risk return benefits for New Zealand investors? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University - Browning, Rebecca (Massey University, 2005)
Many investors are looking for alternative investment options in todays market as correlations among markets have increased, causing diversification benefits once gained to be diminished. This thesis examines what risk return benefits can be gained by investors from international diversification, especially cross listed securities, and how these benefits may enhance the risk return relationship in the face of extreme events. Extreme events being researched are Russian Ruble Crisis in 1998, September 11 2001, and Argentina Financial Crisis in 2002. It was found that cross listed securities held within a portfolio provided diversification benefits for investors with an improvement in the risk return relationship of lower risk and higher returns. Tested under extreme events it was found that holding cross listed securities within a portfolio mitigated some of the affects demonstrated.
Keywords: Securities; Risk management; Portfolio management